Core-sheath carbon nanostructured fibers for efficient wire-shaped dye-sensitized solar cells - Fang, Xin (Advanced materials (Deerfield Beach, Fla.), 2014)
© 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.